Altered N-Linked Glycosylation in Follicular Lymphoma and Chronic Lymphocytic Leukemia: Involvement in Pathogenesis and Potential Therapeutic Targeting - Hollander, Nurit; Haimovich, Joseph (Frontiers in Immunology, 2017)
B-cell antigen receptor (BCR) expression is indispensable for survival of most B-cell malignancies. In follicular lymphoma (FL), N-linked glycosylation sites are introduced in the immunoglobulin variable region genes. Oligosaccharides added to the acquired sites are unusually of the high-mannose type. These glycans interact with mannose-specific lectins, especially with dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN). Lectin binding to FL triggers persistent activating signals, suggesting that lectins within the tumor microenvironment promote cell survival and proliferation. Insertion of N-glycosylation sites in immunoglobulin variable region genes has been detected in other germinal center-associated lymphomas, specifically in subsets of diffuse large B-cell lymphomas and burkitt's lymphomas, suggesting involvement of altered glycans in pathogenesis of these malignancies as well. Furthermore, the BCR in chronic lymphocytic leukemia (CLL) carries high-mannose oligosaccharides, albeit in the heavy chain constant rather than variable region. The high expression level of the unique glycoform, particularly in the more aggressive unmutated CLL subset, suggests a functional significance for this glycan in CLL. As lectin interaction with the BCR is critical for FL and probably for some other lymphomas, targeting this interaction is considered to be an interesting therapeutic strategy. Reagents for blockade of lectin-BCR interaction may include antibodies against high-mannose glycans and mannose-based oligosaccharide mimics or noncarbohydrate glycomimetics. Moreover, as this interaction triggers signaling pathways similar to those demonstrated for BCR engagement by antigen, BCR signal transduction inhibitors may emerge as effective therapeutics for lectin-driven malignancies.